2020
DOI: 10.1136/bmjopen-2020-039119
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health without clinically measurable benefits among adult users of multivitamin and multimineral supplements: a cross-sectional study

Abstract: ObjectiveMultiple clinical trials fail to identify clinically measurable health benefits of daily multivitamin and multimineral (MVM) consumption in the general adult population. Understanding the determinants of widespread use of MVMs may guide efforts to better educate the public about effective nutritional practices. The objective of this study was to compare self-reported and clinically measurable health outcomes among MVM users and non-users in a large, nationally representative adult civilian non-institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…On the other hand, in the large US study (National Health Interview Survey), vitamin/mineral supplement users reported better overall health than non-users despite apparent differences in clinically measurable health outcomes. Thus, it seems that the widespread use of DS in adults may be a result of an individual's positive expectation that such product use leads to better health outcomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the large US study (National Health Interview Survey), vitamin/mineral supplement users reported better overall health than non-users despite apparent differences in clinically measurable health outcomes. Thus, it seems that the widespread use of DS in adults may be a result of an individual's positive expectation that such product use leads to better health outcomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Certain dietary supplements, such as vitamin D, which is key ingredient of the Health & Her supplements, have been demonstrated among menopausal women (13). Alternatively, this outcome may be related to placebo effects, as individuals who had recently started taking Health & Her supplements may have a positive expectation that the supplement will lead to better health outcomes, and these positive expectations may have manifested as self-reported health improvements (14). Thus, individuals who recently purchased Health & Her supplements may have been more likely to report benefits from doing so.…”
Section: Discussionmentioning
confidence: 99%
“…These results are constant with the findings of other studies [ 17 , 18 ]. One cross-sectional study conducted in the United States of America (USA) demonstrated a higher MVMM prevalence in females as well [ 19 ]. In another study in Japan with 1,776 participants, females were far more likely to report supplement use than males [ 20 ].…”
Section: Discussionmentioning
confidence: 99%